Mobility-aware dynamic service placement for edge computing - Liu, Gang; Wang, Jiawei; Tian, Yumin; Yang, Zhenhua; Wu, Zhenping (EAI Endorsed Transactions on Internet of Things, 2019)
Edge computing provides capabilities similar to traditional cloud computing at network edge closer to users. Oﬄoading applications from the cloud to the edge of the network can eﬀectively diminish the latency of users waiting for applications to improve their quality of service(QoS). Due to the user mobility, however, the distance between the user and the edge device is constantly increasing, resulting in a degradation of the user’s QoS. To satisfy the QoS of mobile users, applications should be dynamically migrated to follow the user mobility. In this paper, we propose a mobility-aware dynamic service placement policy that reduces the number of virtual machine migrations and diminishes user-perceived latency simultaneously. The proposed scheme ﬁlters out the invalid migration that the user handoﬀs to another access point before the migration is completed. The simulation trials demonstrate that our solution improves the QoS of users and reduces the number of application migrations.